Serum transferrin receptor-ferritin index as a marker of iron deficiency anemia in active inflammatory bowel disease patients in Indian population - Gujjarlapaudi, Deepika; Veeraiah, Namburu; Naveed, Syed Hassan; Reddy, Duvvuru Nageswara (International Journal of Research in Medical Sciences, 2021)
Background: Anemia is most common complication in IBD (inflammatory bowel disease). The aim of the study was to assess the sTfR-F (soluble transferrin receptor-ferritin) index as early marker of IDA (iron deficiency anaemia) in IBD. Methods: Retrospective cross sectional study has 480 cases of IBD (group I ) with controls 220 (group II), CBP, serum hsCRP, serum iron, TIBC (total iron binding capacity), sTfR, ferritin, fecal calprotectin, vitamin B12, folic acid were assessed. Results: In study I, group I was compared with group II showed (66.5%) patients had active disease and in that 65.0% of UC, 32.1% of CD and 2.9% others colitis had anemia. In study II, subgroup I 56.4% had IDA subgroup II 7.3% had ferritin between 30-100 ng/ml combi subgroup III 23.3% had ferritin>100 ng/ml (ACD, anaemia of chronic disease) subgroup IV 5.6% had vitamin B12 and folic acid deficiency excluding sTfR-F analysis. In study III, subdivided to identify IDA with sTfR-F index as group A 60.8% had sTfR-F index>2, group B 32.6% had sTfR-F index=1-2 and group C 3 (6.2%) had sTfR-F index<1. Intially diagnosed IDA was 56.4%, in addition with group A, IDA has increased by 66.5%. In study IV, in IDA, sensitivity of sTfR-F index was100%, sTfR 89% and SF 85%. Specificity of sTfR and sTfR-F index were 80.60% and SF has low specificity 73.90%. In study V, a statistical significance was seen more in female than male and in children than in adults with sTfR-F index in IDA. Conclusions: sTfR-F index as an early diagnostic marker, in differentiating IDA, ACD and combi in IBD patients.